PERAN DIMENSI TECHNOLOGY ACCEPTANCE MODEL DALAM PEMANFAATAN GEMINI AI TERHADAP LITERASI DIGITAL MAHASISWA - Amalia Rahmah; Annisa Nasywa Salsabila; Nurul Janah; Shelly Pramudiawardani (Universitas Tribhuwana Tunggadewi, 2026)
Digital literacy is a critical competency for information technology students in the era of artificial intelligence. The use of Generative AI, such as Gemini, in academic learning has moved beyond mere technology adoption, fostering a broader understanding of its role in students' academic lives. Gemini AI has the potential to enhance students' digital literacy. However, this potential does not manifest uniformly the extent to which Gemini AI contributes to students' digital literacy depends on how they receive and interact with the technology, including perceptions of ease of use and usefulness, attitudes, intentions, and actual use. This study therefore aims to examine the role of each Technology Acceptance Model (TAM) dimension in the use of Gemini AI toward students' digital literacy. Data were collected via a questionnaire from 107 Gemini AI users at STT Terpadu Nurul Fikri and analyzed using simple and multiple linear regression. Results show that Gemini AI use significantly contributes to students' digital literacy, explaining 35.9% of its variance. Among the five TAM dimensions, only Perceived Ease of Use demonstrated a positive and statistically significant partial effect (?=0.322), while Perceived Usefulness showed a negative effect. These findings indicate that students' digital literacy is more strongly determined by the ease and comfort of interacting with Gemini AI than by perceived usefulness alone. The results of this study can be considered by STT-NF in designing a strategy for utilizing Gemini AI that focuses on ease of use to support improving students' digital literacy.